Chironomidenstudien. I. Pseudodiamesa belingi n. sp. - Fittkau, Ernst Josef (Contributions to Entomology = Beiträge zur Entomologie, 1954)
Nomenclatural Actsbelingi Fittkau, 1954 (Pseudodiamesa), spec. n.